The empirical consequences of trade sanctions for directly and indirectly affected countries - Jonas Frank (FIW - Research Centre International Economics, 2017)
Economic sanctions are a popular diplomatic tool for countries to enforce political demands abroad or to punish non-complying countries. There is an ongoing debate in the literature if this tool is effective in reaching these goals. This paper adds to the literature by treating sanctions like a negative form of trade agreements. In order to quantify the direct effects of sanctions on the trade flows between countries I make use of a gravity equation controlling for country pair, importer-year, and exporteryear fixed effects. The estimates reveal that there is a significant decrease in the value of trade after the introduction of sanctions. In a second step, trade diversion is introduced as a potential instrument for countries to soften the negative impact of sanctions. However, the estimates reveal no evidence for trade diversion.
Keywords: 330; gravity; international trade; trade sanctions